Trade openness and economic growth: a cross-country empirical investigation - Ulasan, Bülent (2008)
In this dissertation, we empirically investigate the relationship between trade openness and economic growth across countries over the period 1960-2000. The main contribution of this dissertation is that we handle the model un-certainty problem by employing model averaging techniques, instead of estimating and reporting a number of cross-country growth regressions. Differently from many previous cross-country growth studies, our findings do not support the proposition that openness has a direct robust relationship with long run economic growth. However, we conclude that economic institutions and macroeconomic uncertainties relating to inflation and government consumption are key factors in explaining economic growth in the long run.